IMPLEMENTASI METODE FP-GROWTH DALAM ANALISA POLA PEMBELIAN PELANGGAN PADA SWALAYAN PANTES PATI BERBASIS WEB: IMPLEMENTATION OF THE FP-GROWTH METHOD IN WEB-BASED ANALYSIS OF CUSTOMER PURCHASE PATTERNS AT PANTES PATI SUPERMARKET - Salum Ainayya Alfatikhah; Supriyono Supriyono; Soni Adiyono (LPPM Universitas Abdurrab, 2026)
Swalayan Pantes, located in Pati Regency, is a retail store that provides daily necessities. However, its current data processing still relies on manual management through Microsoft Excel, which is less efficient for conducting sales analysis. This study aims to develop a web-based purchasing pattern analysis system by employing the Frequent Pattern Growth (FP-Growth) method. The methodological stages include determining support values, constructing the FP-Tree, generating the conditional pattern base, building the conditional FP-Tree, identifying frequent itemsets, and calculating confidence values. Based on 1,725 transaction records collected between January 2025 and July 2025, the study identified 13 items most frequently purchased together, with a confidence threshold of 60% and a minimum support value of 5. The FP-Growth method was subsequently implemented into a web-based system, complemented with additional features such as “Pindah” (Move) and “Promo” (Promotion), to facilitate decision-making and follow-up actions derived from the analysis results.